THE EXPERIENCE OF 2021 ARABIC LANGUAGE EDUCATION STUDENTS STATE ISLAMIC UNIVERSITY OF NORTH SUMATRA IN DEALING WITH THE PROBLEMS OF LEARNING NAHWU: A PHENOMENOLOGICAL STUDY - Dini Febria Arifina; Khoirul Jamil (Universitas Islam Negeri Sumatera Utara Medan, 2023)
This research aims to find out the experiences of PBA students in 2021 in dealing with problems that arise in learning nahwu. The research method used is a qualitative research method with a phenomenological approach. The data collection techniques used in this research are observation and in-depth interviews with PBA students in batch 2021, totaling 4 people who feel they have encountered problems in learning nahwu. The data analysis technique used is Interpretative Phenomenological Analysis (IPA) with the stages of preparing interview transcripts, initial recording, formulating themes, making patterns of informants' experiences and reporting results. The results of the study found that from the problems experienced, making students experienced in dealing with these problems, including: First, following the Arabic language course bimble in various non-formal institutions or outside of lecture learning hours. Second, conducting group discussions with friends who understand the material better. Third, looking for learning resources that are more innovative and fun. Like through youtube, tiktok and instagram.Keywords: Nahwu, Phenomenology, Problems